PENGARUH MODEL CTL TERHADAP MOTIVASI DAN HASIL BELAJAR PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Sari, Eka Widya; Enawaty, Eny; Melati, Husna Amalya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to determine whether there is a difference between the motivation of students' learning grade X IPA MAN 1 Pontianak on the material of electrolyte and non electrolyte solution using contextual teaching and learning model and using conventional model, whether there is difference between student learning outcomes in electrolyte and Non electrolytes using contextual teaching and learning models and using conventional models, and determine how much effect the contextual teaching and learning model of student learning outcomes. The samples in this research are the students of class X IPA1 as control class and class X IPA3 as experiment class. The result of data analysis using U-Mann Whitney test showed Asymp value. Sig. (2-tailed) of 0.038 so that Ho is rejected (Ha accepted), it indicates the difference of learning motivation of control and experiment class students. Hypothesis test of learning result using U-Mann Whitney test yield Asymp value. Sig. (2-tailed) of 0.00, so Ho is rejected, this shows the difference of the students' learning outcomes of the control class and the experimental class. Learning using contextual teaching and learning model provides an increase in learning outcome of 65.3%.Keywords: Contextual teaching and learning, learning motivation, learning result, electrolyte and nonelectrolyte solution